Factors Affecting Intention to Use of Government Websites in Thai Elder: The Webqual Model - Nilpong, Rattanaporn; Thanasopon, Bundit (My University, 2020)
The main objective of this research is to identify factor affecting the intention to use of government websites among Thai Elderly. The proposed model was framed by the Webqual conceptual framework. From the literature review we were able to identify 7 factors, namely Completeness of Information, Tailored Communication, Navigation, Ease of Understanding, Multimedia, Trust and Response time. We argue that these factors directly influence elder people's intention to use government websites in Thailand. The data were collected with a questionnaire asking 250 elders in Thailand. A total of 88 valid questionnaire copies were analyzed using multiple regression analysis. The results suggest that Completeness of Information, Tailored Communication and Trust are significantly and directly affect Thai elders' intention to use government website. These could help the government in their effort to digitalization the services and improve the accessibility and quality of services for elder people in Thailand.
Keywords: Government websites; Intention to Use; TAM; Technology Acceptance Model; Thai elder; Theory of Reasoned Action; TRA; Webqual Framework; Website quality measurement